Bildsame Schönheit: Zur Integration des Ästhetischen im mathematikdidaktischen Bildungsdiskurs (mathematica didactica, 2021)
The beauty of proofs and the orems as well as treating mathematics as an art are concerning the relationship between the individual and mathematical objects beyond their applicability. Based on general research in the philosophy of mathematics aesthetic value judgment in mathematical practice is describable as an interplay of properties being inherent in the objects on the one hand and epistemic and emotional experiences on the other. Against this background the following paper shows expectable impact on the subjects Bildung by becoming aware of mathematical beauty and the process of its production as well as by working creatively. By this the aesthetical dimension of Allgemeinbildung turns out to bea fruitful but neglected extension of common concepts of mathematical Bildung.